Morphotectonics of the Bogd fault and the Orog Nuur Basin (southern Mongolia) - UAV surveys, GPR locations and alluvial fan mapping - Jorien L N van der Wal; Veit Nottebaum; Boris Gailleton; Georg Stauch; Christopher Weismüller; Ochirbat Batkhishig; Frank Lehmkuhl; Klaus Reicherter (PANGAEA, 2024)
The database consists of two shapefiles that show the locations of unmanned aerial vehicle (UAV) surveys and of ground-penetrating-radar analyses. The raw data of these surveys may be shared upon request and after publication. Additionally, one shapefile consisting of geomorphological alluvial fan mapping has been added. UAV surveys were conducted with the DJI Phantom 4 (12 MP sensor) and DJI Phantom 4 Advanced (20 MP sensor) drones to create high-resolution digital elevation models (DEMs). In the extquotesingleDrone_areas extquotesingle shapefile, the column extquotesingleName extquotesingle refers to the survey name given in the field, and the column extquotesingleReference extquotesingle indicates the catchment referred to in van der Wal et al. (submitted to Geomorphology in 2019). The extquotesingleGPR_profiles extquotesingle shapefile includes the locations of all GPR data collected in September 2017. All measurements were conducted using a SIR-3000 field computer and a 100 MHz GSSI radar antenna (model 3207A), with a survey wheel (model 620) to calibrate distance data. Dielectric permittivity values were set between 4 and 7. Van der Wal et al. (submitted to Geomorphology in 2019) includes GPR profiles 005, 003, 006 (G-1, G-2, G-3, respectively) and 064 (Hustiyn am). The extquotesingleAlluvialFanLevels extquotesingle shapefile includes a geomorphological map of alluvial fans along the Ikh Bogd mountain front. The method for mapping is discussed in van der Wal et al. (submitted to Geomorphology in 2019). Some minor alluvial fan levels were excluded from publication (e.g. levels 1+ and 1t) because of their minor scale and lack of relevance in the discussed context.